Minimum summer temperatures in the southeast of the iberian peninsula through satellite thermographies - Espín-Sánchez, David (Revista de Estudios Andaluces, 2021)
The latitudinal position of the southeast of the Iberian Peninsula generates high average temperatures (between 25 and 30oC) during the summer season, although its complex orography and the important lapse rate (LR) give rise to important differences in minimum temperatures, influenced by intense processes of nocturnal temperature inversion (ITN) in inland valleys. The increase of new meteorological stations and the rise in the density of observation networks, together with the implementation of its own network in cold air pools (CAP) in the provinces of Murcia, Albacete or Jaén, leads to a greater understanding of the distribution of surface temperatures. The main objective of the research is the generation of cartography (thermographs) that reflects the distribution of night temperatures in the southeast of the Iberian Peninsula, carried out through the treatment of satellite products (VIIRS LST Band I5 of the SUOMI-NPP satellite). Together with the use of satellite images (thermography), it is possible to analyze in detail the thermal contrasts that exist during the hottest days of summer through 147 weather stations and recording thermometers (July 15 to August 15) of the year 2017 to 2020. Verification of the thermographs used (Band I5 product) shows a notable statistical adjustment (R2 of 0.87), with a Bias and RMSE of -0.2 and 1.83oC respectively. The cartography is carried out for the differences in the provinces that make up the SE of the Iberian Peninsula (Alicante, Albacete, Murcia, Jaén, Granada and Almería), with daily thermal differences in minimum temperatures of up to 23.4oC between inland valleys and coastal areas.